Geodiversity characterization of the Danxiashan UNESCO Global Geopark of China - Liuqin Chen; Fusheng Guo; Chongjian Shao; Dingding Du; Fang Chen; Ming Luo (International Journal of Geoheritage and Parks, 2022)
The Danxiashan UNESCO Global Geopark (Danxiashan UGGp) is located in Shaoguan, northern Guangdong Province of South China, and was approved as such by the Global Geoparks Network in 2004. It is an ideal site for geodiversity and geoheritage studies as well as a centre for geoeducation owing to its importance in understanding the geodynamics of South China during late Mesozoic and being the most representative danxia landscape (a red beds landscape characterized by well-developed cliffs and developed dominantly on hard conglomerates and sandstones) in the humid subtropical climate of China. The methods of field investigation and literature reviews were applied to document geodiversity characterization of the Danxiashan. The study area is characterized predominately by well-developed Late Cretaceous red beds deposited in alluvial fan and desert environments within a faulted continental basin. The red beds were uplifted during the Himalayan orogenic cycle (ca. 40 Ma to present) and dissected by faulting and jointing to form prominent escarpments and a variety of erosional landforms in tandem with weathering, water erosion and rockfalls. The danxia landscape of Danxiashan is composed of mesas, peaks, cliffs, canyons, rock walls and pillars with dominant bedrock of reddish conglomerates and sandstones. It is designated as the World Heritage ‘China Danxia’ with other five sites in South China owing to its exceptionally beautiful and distinctive landscape as well as diversified geological features and landforms. As one of the earliest and best developed geoparks in China, an assessment and summary of the geodiversity of Danxiashan sets a practical example in formulating long-term strategies in geotourism and geoeducation for geopark development in China and other countries.